Wormhole attack detection in internet of things - Sneha Deshmukh Bhosale, Mrs.; S. S. Sonavane, Dr (International Journal of Engineering and Technology, 2018)
Number of devices connected to the internet will increase in near future because of more applications arising in Internet of Things (IoT). These devices are resource constrained in terms of battery and processing power hence inserting security in constrained devices is going to be very challenging. There are many attacks taking place in Internet of Things like wormhole attack, sinkhole attack, hello flooding attack, cybil and clone ID attack etc. In this paper we are proposing a method to identify the wormhole attack taking place at routing layer of IoT. Wormhole attack is one such attack that has been recently discovered. Wormhole attack is a very severe and challenging attack because of the fact that it can be launched against any protocol and also due to its ability to be effective in case of encrypted trafï¬c. Threats due to Wormhole attack are alterations in network, can cause failure of location dependent protocols, can penetrate wrong route/topology information into the network and defeating the purpose of routing algorithms. In this paper we are discussing various types of Intrusion Detection Systems available for IoT attacks. We have also proposed an Intrusion Detection System (IDS) for Wormhole Attack.Â Â